Near-complete genome sequence and seed transmission evaluation of physalis rugose mosaic virus from southern Brazil Sequência do genoma completo e avaliação da transmissão por sementes do physalis rugose mosaic virus no sul do Brasil - Savi A.* (2021)
© 2021, Universidade Federal de Santa Maria. All rights reserved.Physalis rugose mosaic virus (PhyRMV) causes severe damage to Physalis peruviana L., affecting vegetative parameters, fruit quantity and quality. The aim of this study was to perform a molecular characterization of PhyRMV associated with P. peruviana from commercial fields in the municipality of Lages, Santa Catarina State, Southern Brazil, and to evaluate its transmission by seeds. Plants displaying mosaic, dwarfism, and leaf malformation symptoms were collected from P. peruviana. Double-stranded RNA was extracted and submitted to cDNA library synthesis and high-throughput sequencing (HTS). For the virus transmission assay, seeds from PhyRMV-infected plants were used, and viral infection in seedlings was verified using symptomatic and molecular diagnosis. PhyRMV RNA has 4162 nucleotides (nts) and a genomic organization similar to that of other sobemoviruses and shares 97% nt identity with the previously characterized PhyRMV Piracicaba isolate. Results indicated the unlikely transmission of PhyRMV by physalis seeds.